In Silico Study : Phyllanthus Niruri L as Immunomodulator Against Covid-19 - Mohammad Sukmanadi1 , Emy Koestanti Sabdoningrum2 aditya Tri Ananda3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
In December 2019, a mysterious case of pneumonia was first reported in Wuhan, Hubei Province. Thesource of transmission of this case is still unknown, but the first case was linked to the fish market in Wuhan.From 18 December to 29 December 2019, there were five patients treated with Acute Respiratory DistressSyndrome (ARDS). 2 From 31 December 2019 to 3 January 2020 this case increased rapidly, marked by 44cases reported. In less than a month, the disease has spread to other provinces in China, Thailand, Japan andSouth Korea. This virus can be transmitted from human to human and has spread widely in China and morethan 190 other countries and territories. On 12 March 2020, WHO announced COVID-19 as a pandemic.As of March 29, 2020, there were 634,835 cases and 33,106 deaths worldwide. While in Indonesia, 1,528cases were confirmed with COVID-19 and 136 deaths. Phyllanthus niruri L (meniran) is one type ofimmunostimulator that can improve the immune system in animal experiments and humans. This studyaims to determine Phyllanthus niruri L as an immunomodulator for Covid-19. From the results of researchconducted that Phyllanthus niruri L can improve the activities and functions of several non-specific immunesystem components and specific immune systems, both soluble and cell-related forms. The conclusion fromthe results of this study is Phyllanthus niruri L as an immunomodulator for Covid-19.